A qualitative investigation into the effectiveness of a housing navigator program linking justice-involved clients with recovery housing - Jodie M. Dewey; Patrick Hibbard; Dennis P. Watson; Juleigh Nowinski Konchak; Keiki Hinami (BMC, 2024)
Abstract Background Roughly 24-36% of people who are incarcerated in the U.S. are formally diagnosed with opioid use disorder (OUD). Once released, individuals involved with the criminal legal system (CLS) face increased risks of return to use and fatality and are 129 times more likely to die from an overdose within the first two weeks of release compared to those without CLS involvement. People who are CLS-involved and who are seeking a recovery living environment can access temporary stable housing through recovery homes. However, entering a recovery home can be difficult due to fragmentation among recovery housing organizations and their non-uniform application and screening procedures. A navigation pilot program was implemented to provide clients with recovery home placement advice, pre-screening, and referrals in Cook County, IL. Existing research on recovery homes has rarely examined the importance of recovery housing navigation for enhancing service engagement among CLS-involved individuals receiving medications for OUD. Methods Semi-structured qualitative interviews were conducted with 22 clients and three recovery housing navigators as part of a program evaluation of the navigation program pilot. Qualitative software was used to organize and qualitatively analyze transcripts through several rounds of coding producing emergent themes, which were then triangulated, and expanded using navigator data. Results Clients seeking recovery home services reported multiple prior challenges securing safe and supportive recovery living environments. Despite low initial expectations, clients described their interactions with housing navigators in favorable terms and felt navigators worked with them effectively to identify and meet their housing and substance use needs in a timely manner. Clients also commented on their partnerships with the navigator throughout the process. Interactions with navigators also calmed fears of rejection many clients had previously experienced and still harbored about the process, which bolstered client-navigator relationships and client motivation to engage with additional services. Conclusion Evidence from this study suggests recovery home navigation can improve the speed and efficiency with which clients are connected to appropriate services that are tailored to their specific needs as well as increase client motivation to engage with a myriad of recovery services.